Faculty advising system - Abu Ajadayel, Suha; Shehadeh, Asma (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2005)
Ppu is one the most popular universities in Palestine, the college of engineering and technology at ppu consist of three departments: the department of civil and architecture engineering , department of mechanical engineering, and the department of electrical and computer engineering. Each program in these department has a number of sections, each one has been managed and recognized by a faculty adviser who is responsible for each student on his section, the adviser provides students with information about the faculty or the departments curriculum structure that can help students to decide courses the need and to assist them in choosing various courses. During each semester , the faculty advisers ask students to fill out a pre-registration card . faculty advisers according to this card obtain a report with statistical result that the courses and the number of students needed.
no of pages 72, 18653, هندسة حاسوب 9/2005, in the store
Keywords: Faculty advising systems